Commuting Dynamics and Their Implications for Physical and Psychological Well-Being of Tertiary Institution Workforce in Kwara State, Nigeria - Alhaji Ibrahim Isah (INTERNATIONAL JOURNAL OF HEALTH AND PHARMACEUTICAL RESEARCH, 2026)
The daily commuting burden borne by tertiary institution staff constitutes an underexplored yet consequential determinant of workforce health in sub-Saharan Africa. Against the backdrop of rapidly expanding urban transport challenges in Nigerian mid-sized cities, this study investigates commuting dynamics and their implications for the physical and psychological well-being of tertiary institution workforce in Kwara State, Nigeria. Employing a cross-sectional survey research design, the study administered structured questionnaires to 412 academic and non-academic staff drawn from five tertiary institutions across Ilorin metropolis, selected through stratified random sampling. The study analyzes commuting characteristics encompassing mode, distance, duration, frequency, and out-of-pocket cost; evaluates self-reported physical health outcomes; and assesses psychological well-being indicators comprising perceived stress and anxiety levels. Findings reveal that over 72% of respondents depend on commercial motorcycles (Okada) and tricycles (Keke) as primary commuting modes. Approximately 68.4% travel distances exceeding 10 km daily, while 61.7% spend more than 60 minutes commuting one way. Monthly commuting costs consume between 15% and 30% of staff monthly earnings for the majority of respondents. Musculoskeletal symptoms, principally back pain, neck pain, and knee discomfort — were the most prevalent physical health complaints (74.3%), followed by fatigue (68.9%) and headaches (52.4%). Psychological stress indicators were significantly elevated among long-distance and high frequency commuters. Multiple regression analysis confirms that commuting duration (β = 0.412, p < 0.001), mode of transport (β = 0.287, p < 0.001), and commuting cost (β = 0.193, p = 0.003) are statistically significant predictors of composite health outcomes (F₅⁄₆₀₆ = 23.614, p < 0.001; R² = 0.419). The study recommends institutional shuttle services, staff housing proximity initiatives, road infrastructure improvements, and adoption of digital transport management platforms as priority interventions.